ChemInform Abstract: Synthesis, Single Crystal Growth and Properties of Sr5Pb3ZnO12. Issue 48 (2nd December 2014) - Winiarski, M. J.; Szreder, N. A.; Barczynski, R. J.; Klimczuk, T.
Abstract Polycrystalline Sr5Pb3ZnO12 is prepared by firing a stoichiometric mixture of SrCO3, Pb3O4, and ZnO in air (alumina crucible, 800 °C, 36 h).The compound crystallizes similar to the known compounds Sr5Pb3MO12 (M: Co, Ni, Cu) in the space group P<alternatives> <![CDATA[6]]> <inline-graphic xlink:href="ark:/27927/pgh2bsnpf8m" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /></alternatives>2m (powder XRD).